DAMPAK COVID-19 TERHADAP PENDAPATAN PEMBUDIDAYA IKAN NILA (Oreochromis niloticus) DALAM KARAMBA JARING APUNG DI DESA JEMBAYAN KECAMATAN LOA KULU: Abstrak, Pendahuluan, Metode Penelitian, Hasil dan Pembahasan, Kesimpulan dan Saran, Daftar Pustaka. - Tania Maulina Simamora; Heru Susilo; Qoriah Saleha (2339-1324, 2024)
This research began in November 2021 – August 2022 in Jembayan Village, Loa Kulu District, Kutai Kartanegara Regency. The purpose of this study is to determine the amount of income and analyze the impact of the pandemic before and during Covid-19 on tilapia farmers in floating net karamba. The purpose of this study is to determine the amount of income and analyze the impact of the pandemic before and during Covid-19 on tilapia farmers in floating net karamba. There were 15 respondents studied in this study. Data analysis of the study obtained the final results, namely the average income of cultivators was Rp. 23,737,861 during Covid-19 and Rp. 34,752,681 before Covid-19. The final result of income can be explained that the impact of the Covid-19 pandemic has an effect on reducing the income of cultivators. This happens because market demand and fish prices are declining while the price of fish feed always increases during the Covid-19 pandemic.This research began in November 2021 – August 2022 in Jembayan Village, Loa Kulu District, Kutai Kartanegara Regency. The purpose of this study is to determine the amount of income and analyze the impact of the pandemic before and during Covid-19 on tilapia farmers in floating net karamba. The purpose of this study is to determine the amount of income and analyze the impact of the pandemic before and during Covid-19 on tilapia farmers in floating net karamba. There were 15 respondents studied in this study. Data analysis of the study obtained the final results, namely the average income of cultivators was Rp. 23,737,861 during Covid-19 and Rp. 34,752,681 before Covid-19. The final result of income can be explained that the impact of the Covid-19 pandemic has an effect on reducing the income of cultivators. This happens because market demand and fish prices are declining while the price of fish feed always increases during the Covid-19 pandemic.